KOMPOSISI KARAWITAN ISMUNING CAHYA: INTERPRETASI KEESAAN TUHAN MELALUI TOKOH SEMAR - Danis Sugiyanto; Sigit Setiawan (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2020)
This work is entitled "Ismuning Cahya", is a work of contemporary Javanese gamelan music composition with the theme "the form of the Oneness of God” represented by the wayang character, Semar. The purpose of the creation of this works is to prove the existence of contemporary music (gamelan), as a reference for gamelan students who are interested in creating works of art (music). The output of this artistic research work is in the form of works (both live and/ or audio documentation) and scientific works which contain the process of developing the works "Ismuning Cahya". From there, it is hoped that this work will be able to become a model for the creation of works of art, especially the creation of contemporary gamelan.